DAMPAK PROGRAM PENGEMBANGAN USAHA AGRIBISNIS PEDESAAN (PUAP) TERHADAP PENDAPATAN PETANI DI KABUPATEN SUMBAWA - Sri Rahayu; Igo Sukmawanto (Jurnal Ekonomi & Bisnis, 2023)
This study aims to examine the impact of the Rural Agribusiness Development (PUAP) program on farmers' income in Sumbawa Regency. This research is a comparative research conducted to compare the income of farmers in Sumbawa Regency before and after receiving PUAP assistance. The population in this study were all farmers in Sumbawa Regency who received PUAP program assistance, totaling 100 people so that the entire population would be taken as a sample. Data collection was carried out using a structured interview technique using a list of questions that had been prepared by the researcher. The data analysis technique in this study was carried out using comparative analysis techniques with the two-average difference test approach which included paired samples statistics test, paired samples correlations test, and paired samples test. The results of this study indicate that there are differences in the income level of farmers in Sumbawa Regency before and after the PUAP program. After the PUAP program, the average amount of income earned by farmers in Sumbawa Regency has increased compared to before the PUAP program. Thus, the PUAP program has a positive impact on the income of farmers in Sumbawa Regency. That is, the greater the PUAP program assistance received by farmers, the income earned by farmers will also increase.